Central bank digital currencies: Digital Yuan and its role in Chinese digital economy development - Jianwei Chen; Igor O. Nesterov (RUDN Journal of Economics, 2023)
Under the impact of financial technology and digital currency, “central bank digital currency” has become an international hotspot in recent years and is also one of the current research and development priorities of China’s central bank. Preparations for China’s digital RMB began as early as 2014, and in 2017 China’s central bank clearly announced that it would fully issue the digital currency. The launch of the digital RMB is a major reform and innovation in the historical development of China’s currency. China’s issuance of a central bankdigital currency will help enhance the status of the People’s Bank, strengthen the effectiveness of monetary policy, improve macro-prudential management capabilities, and promote cross-border RMB payments, etc. Up to now, China has started pilot tests in some cities, such as Shenzhen, Xian, Chengdu Suzhou. Currently, China’s digital RMB has been tested for the public, with features such as unlimited legal compensation, moderate anonymity, national statutory, dual offline payment, no cost of transaction and centralized management. With the rapid development of scientific information technology and the intensification of international competition, the digitalization of currency has become an irreversible trend. The purpose of this study is to identify the practice of digital Yuan and its role in Chinese digital economy development. The discussion tasks of this paper can be summarized as follows. Clarify the definition of digital Yuan; assess the operational model of digital Yuan; evaluate the operating framework of digital Yuan; identify the features and merits of digital Yuan application. This research adopts case study of China CBDC and literature analysis methods to analyzed the concept, characteristics and design principles of digital RMB. Then it investigates the role of digital RMB for the development of China’s digital economy, which will provide an important basis for understanding and advancing the domestic research on the central bank’s digital currency. For example, digital Yuan plays a key role in facilitating data productivity, driving digitalization of public payment scenarios and opening a healthy digital economy system.